2019
DOI: 10.2214/ajr.18.20405
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cervical Nodal Necrosis Observed in Preoperative CT and MRI of Patients With Tongue Squamous Cell Carcinoma and Cervical Node Metastases: A Retrospective Study

Abstract: recent technical advances in surgical management and radiation therapy, some patients inevitably experience locoregional recurrence or distant metastases within 2 years after treatment completion [6]. Because the importance of precision medicine or individually tailored treatment has been emphasized in cancer treatment, imaging biomarkers that stratify patients at risk for treatment failure (TF) would be useful for identifying patients who could be candidates for additional treatment or deescalation treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Baik et al and Lan et al had highlighted the prognostic value of cervical node necrosis in CT and MRI studies [16,21]. In our analysis, the survival outcomes in the CNN group were critically poorer than those in the non-CNN group and similar to those of patients with higher N stage disease without CNN.…”
Section: Discussionsupporting
confidence: 45%
“…Baik et al and Lan et al had highlighted the prognostic value of cervical node necrosis in CT and MRI studies [16,21]. In our analysis, the survival outcomes in the CNN group were critically poorer than those in the non-CNN group and similar to those of patients with higher N stage disease without CNN.…”
Section: Discussionsupporting
confidence: 45%
“…This finding was similar to several previous studies, which have shown that the large cervical SCCs tended to generate central necrosis in either the primary tumors or metastatic lymph nodes. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…e RNN is one of the common deep learning algorithms. It is a type of algorithm that takes sequence data as input and recursively in the direction of sequence evolution, its nodes are connected in a chain, and it is featured with memory, parameter sharing, and Turing completeness [17,18]. It has great advantages when learning the nonlinear features of the sequence.…”
Section: Discussionmentioning
confidence: 99%